Effect of Chitosan, Clay, and CMC on Physicochemical Properties of Bioplastic from Banana Corm with Glycerol. - Sugiharto, Agung; Syarifa, Adilla; Handayani, Nindita; Mahendra, Rizky (Universitas Negeri Semarang, 2021)
Bioplactic from banana corm and glycerol has been studied in this research. In addition, the physical chemical properties of it has been improved by adding chitosan, clay and CMC as filler and glycerol as plasticizer. Plastic that produced form organic material such as starch usually has poor properties in physical and mechanical. Composition variation of chitosan, clay and CMC as filler then combined by variation of glycerol as plasticizer have produced significant improve of the bioplastic physical properties. Properties of the bioplastic that studied in this research was focused to biodegradation, elongation, and tensile strength. The addition of fillers and plasticizers is carried out to produce a better bioplastics. This study used 3 variations of the filler composition : 4, 5, and 6 grams and 2 variations of the plasticizer composition: 1 ml and 2 ml. The bioplastics that produced were tested for tensile strength, elongation, and biodegradation of the soil for 7 days. The best tensile strength results is 8.43 MPa for bioplastic that using CMC fillers. On the other side, the best elongation percentage is 9.87% for bioplastic which using CMC fillers. The bioplastic that added Clay as filler can be degraded up to 100% in 7 days.